Family demographic processes and in-work poverty: A systematic review. (June 2022) - Polizzi, Antonino; Struffolino, Emanuela; Van Winkle, Zachary
Abstract: This article reviews ever published quantitative evidence on in-work poverty and family demographic processes in OECD and EU-28 countries. Despite the increasing attention to in-work poverty in Europe and beyond, a comprehensive and critical review on how family demographic processes shape in-work poverty risks is still missing. In this systematic review, we first provide a quantitative review of results from analyses that estimated the association between in-work poverty and parental home leaving, union formation, marriage, parenthood, and dissolution of non-marital and marital unions. This allows us to formulate tentative conclusions about whether and in which direction family demographic processes are associated with in-work poverty. Second, we discuss in detail conceptual and methodological advances in in-work poverty research, such as longitudinal analytical designs or attempts to make in-work poverty research more sensitive to policy context, gender, and the life course. Our review highlights theoretical and methodological challenges for future studies linking in-work poverty and family demography. Highlights: 30 studies and 86 analyses linking family demographic processes to in-work poverty were systematically reviewed. Roughly 80 percent of analyses reported the risk of in-work poverty increased with children. 60 percent of analyses indicated that being in a union decreased the risk of in-work poverty. The majority of the few studies considering union dissolution indicated that it increased the in-work poverty risk. Results supported common hypotheses and highlighted the impact of methodological considerations on studies' conclusions.